Comparison of the complications of en-block and piecemeal endoscopic mucosal resection of large laterally spreading tumors - Tkachov, V. S.; Kiosov, O. M.; Ткачов, Владислав Сергійович; Кіосов, Олександр Михайлович (My University, 2025)
Aim. To compare the incidence of intraprocedural bleeding, perforation, and six-month recurrence following en bloc EMR versus pEMR of non-invasive LSTs ≥ 20 mm.
Порівняння ускладнень при ендоскопічній резекції слизової фрагментарно і єдиним блоком великих новоутворень товстої кишки, що поширюються латерально